Role of hepatobiliary ultrasound in the diagnosis of choledocolitiasis (2010)
Background Jaundice is a diagnostic approximation that combines different signs and symptoms. Although Endoscopic Retrograde Cholangiopancreatography (ERCP) can be a therapeutic option for this pathology, it is an invasive procedure with morbidity and mortality risks. Therefore, this procedure should be used therapeutically rather than in diagnosis, and other accurate diagnostic procedures should be used first. If hepatobiliary echography can be adapted to detect pathological signs of obstructive jaundice it would be important, since in our context ultrasound is used to determine the possibility of using an invasive test such as ERCP. The objective of the study was to determine what correlation existed between the hepatobiliary ultrasound and ERCP of the biliary tract in those procedures performed at University Hospital de La Samaritana (UHS) between March 1, 2005 and November 1, 2007. Materials and methods This was a retrospective study of diagnostic test results. Information was collected using a closed-ended set of questions. This questionnaire described patient characteristics and findings from hepatobiliary ultrasound and ERCP reports. First, ERCP patients were descriptively analyzed, then sensitivities, specificities and odds ratios (OR) were calculated. Cohen's kappa index was used (?): Po-Pe/1-Pe) to determine the degree of agreement between the tests Results. During the study period ERCPs were performed on 457 patients of whom 271 fulfilled the inclusion criteria. For the diagnosis of biliary tract expansion hepatobiliary ultrasound's sensitivity was 66.5% (CI 95%: 60.2 to 72.5) and its specificity was 65.6% (CI 95%: 46.8 to 81.4). Negative OR was 49%. For the diagnosis of choledocolithiasis hepatobiliary ultrasound's sensitivity was 25.6% (CI 95%: 18.4 to 33.9) and its specificity was 87.7% (CI 95%: 81.0 to 92.7). Conclusions This study confirms that in our context hepatobiliary ultrasound has low sensitivity and specificity for diagnosis of both obstructive biliary disease and choledocolithiasis. In addition it showed low levels of agreement between the findings detected by hepatobiliary ultrasound and ERCP. The use of other diagnostic tools such as endoscopic echography is recommended prior to performing an ERCP when the probability of choledocolithiasis is low to average. This will decrease the risk of comorbidity and mortality among patients. © 2010 Asociaciones Colombianas de Gastroenterología.